Losimpactosdelcáncerdemamaenlaautoimagendelasmujeres (ModaPalavra e-periódico, 2020)
Esteartículoverificalosimpactosdelosefectossecundariosdeltratamientodelcáncerdemamaenrelaciónconlaautoimagendelasmujeres.Seutilizóinvestigacióncualitativaydescriptiva,completadaconinvestigacióndecampo,conunamuestradetresmujeresconcáncerdemama.Luegodeanalizarlosdatos,sepudoverificarqueexistenimpactosenlaautoimagendelamujer,especialmentecuandocomienzanasentirselosefectossecundariosdelostratamientos
Keywords: autoimagen; autoestima; cáncer de mama; mujer